The relationship between maternal periodontitis, adverse pregnancy outcome and miscarriage in never smokers - S. Farrell (ne´e Moore) (Blackwell Synergy, 2006)
Background: It has been postulated that associations between periodontal disease and systemic conditions may be because of the confounding effects of smoking. In addition, studies of this type rarely investigate the adverse pregnancy outcome of miscarriage. Aim: The aim of this prospective study was to investigate a relationship between periodontal disease in pregnancy and subsequent adverse pregnancy outcomes in a population of never smokers. Materials and Methods: Pregnant women were recruited at 12 weeks gestation. Demographic, behavioural and medical data were collected. A periodontal examination was performed and data on each subjects’ pregnancy outcome were collected. Results: A total of 1793 women reported never previously smoking. Of these, 7.3% had a pre-term birth and 0.9% a late miscarriage. As expected in this population, we found no associations between poorer periodontal health and either pre-term birth or low birth weight (LBW). In contrast, the subjects who experienced a late miscarriage had a higher mean probing depth at mesial sites compared with the subjects that gave birth at term (2.69mm versus 2.41 mm, p50.006). Conclusions: There was an association between some measures of periodontal disease and late miscarriage; however, there was no association between periodontitis and pre-term birth or LBW in this population.